Evaluation of Emergence and Vigority of Some Genotypes of Tropical Minor Legume Landraces - Ardyansyah, Fery; Ma'ruf, Amar (Akademi Komunitas Perkebunan Yogyakarta, 2025)
Various tropical pulses such as velvet bean, lima bean, and jack bean are leguminous plants that have legumes cultivated and are found in Indonesia. Legumes are a source of vegetable protein with a protein content ranging from 18% to 25%. The aim of study is to evaluate, assess, and identify genotypes of tropical minor legume landraces that show high emergence and vigor through this research, understanding genetic diversity in populations of tropical minor legume landraces can be obtained. This supports efforts to conserve plant genetic diversity, which is important for maintaining long-term food security and ensuring the survival of ecologically and culturally valuable plant species. The research was carried out at the Hydroponic Screen House, Faculty of Agriculture, University of Asahan, from December 2023 to February 2024. This research aims to evaluate the level of emergence or growth and identify genotypes of tropical minor legume landraces that show high emergence and vigor. The data design in this study used Complete Randomized Design (CRD) which was replicated in 3 replications and analyzed using Analysis of Variant (ANOVA) supported by the Tukey test at the 5% level, also to assist in the process of creating diagrams using the Microsoft Excel application in the insert menu, namely pivotTable, and all data analysis used SPSS application, the observed variables include: emergence, germination rate, vigor index, simultancity growth. Based on the Tukey analysis, the highest emergence is K5, P3, K4, B2, K3, B1, B4, P5, and the lowest is B3. The genotypes with the highest germination capacity were P1, P2, K1, K2, P3, P5, B1, B2, while P4, B4, K3, K4, K5, B3, B5 is the genotypes with the lowest values. The genotype with the highest vigor index is B3, P4, while the lowest is B1, P3. The genotypes with the highest growth uniformity were the P1, P2, P5, P3, B1 genotypes, and the lowest were the genotypes P4, B3, B5, K1.